2020
DOI: 10.1097/ncc.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long Timing of Flushing of Totally Implantable Venous Access Devices When Not Used Routinely

Abstract: Background Flushing and locking of totally implantable venous access devices (TIVADs) is recommended to maintain their patency when not in use. Although manufacturers’ recommendations indicate monthly access for TIVAD maintenance, there is a tendency in real life to prolong this interval. Objectives To assess the effectiveness of prolonged versus short flushing and locking intervals to prevent TIVAD occlusions in adults with cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Some studies have suggested extending flush interval to 2 months, 9,19 and others have suggested prolonging flush interval to 3 months or longer. 10,25,26 Clari et al 27 reported very lowquality evidence of no statistically significant difference in occlusion rates between short and long flush interval. However, they did not conclude whether flush interval could be extended to a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested extending flush interval to 2 months, 9,19 and others have suggested prolonging flush interval to 3 months or longer. 10,25,26 Clari et al 27 reported very lowquality evidence of no statistically significant difference in occlusion rates between short and long flush interval. However, they did not conclude whether flush interval could be extended to a specific time.…”
Section: Discussionmentioning
confidence: 99%
“…A further flushing interval extension to 3 months could even be considered possible, but must be investigated with further clinical trials. 13,14 Like any change in entrenched habits, a proactive effort by the scientific community and the medical industry is advisable to achieve widespread propagation of flushing procedure changes within the medical community. Given these revelations, the manufacturers of TIVAD could review the contents of their IfU for these devices.…”
mentioning
confidence: 99%
“…Hence, it is worth exploring whether prolonging flush interval will affect the incidence of catheter‐related complications. A meta‐analysis found that very low‐quality evidence showed no statistically significant difference in occlusion rates between short and long flush intervals (Clari et al, 2020). This meta‐analysis only concluded that the flush interval could be prolonged but did not conclude the optimal flush interval for TIVAPs (Clari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis found that very low‐quality evidence showed no statistically significant difference in occlusion rates between short and long flush intervals (Clari et al, 2020). This meta‐analysis only concluded that the flush interval could be prolonged but did not conclude the optimal flush interval for TIVAPs (Clari et al, 2020). Other studies have also shown that compared with 4‐week flush interval, prolonged flushing intervals were safe and feasible; however, these studies suggested that the flush interval could be extended for varying amounts of time (Fornaro et al, 2018; Ignatov et al, 2010; Kefeli et al, 2009; Palese et al, 2014).…”
Section: Discussionmentioning
confidence: 99%